Sibambo Studio's Creative Advertising Strategy to Increase Brand Awareness - Prabowo, Monika Yudesta; Muktaf, Zein Mufarrih (UMSU, 2026)
Sibambo Studio is an architectural consulting company that wants to change its communication strategy during the pandemic. Sibambo Studio collaborated with Syafa'at Marcomm to create the creative strategy through to its execution. This research tries to see how the creative process was carried out by Syafa'at Marcomm in solving the Sibambo Studio problem and designing the solution in a creative strategy. This research found the following conclusions; First, in the creative advertising strategy process, the Strategic Planner team always goes through an orderly process of stages. The stages carried out are a creative strategy system or formula that is used repeatedly. Second, the stages, system or formula in a creative strategy consist of pitching and collecting client data, then continuing with creating a client brief, creating a creative brief and finally creative execution. Third, the strategy process to advertising production is carried out jointly through discussions between the Account Executive (AE), Strategic Planner and also the Creative Team. Fourth, market analysis in building a creative brief relies on 4 main pillars, namely relevant, customer, competitor and brand.